Application of Boltzmann’s integration method under non-ideal conditions - Heinke, Lars (Diffusion Fundamentals, 2007)
Boltzmann’s integration method may prove to be a very powerful tool to study the transport diffusion of guest molecules in nanoporous host systems. In many cases, however, the prerequisites for applying this method are not completely fulfilled. In the following, the consequences of these deviations on the accuracy of the obtained results are discussed. It is found that the results of Boltzmann’s integration method can be corrected by different considerations. The discussion is focussed on the concentration profiles observed during the adsorption and desorption of methanol in ferrierite-type crystals as observable by interference microscopy.